Isolation And Antimcirobial Activity Of Lactic Acid Bacteria Against Streptococcus Mutans - Nor Zaihana Abdul Rahman; Rohazila Mohamad Hanafiah; Siti Aisyah Abd Ghafar; Norafiqa Abdullah; Nur Nabilah Azman (Ectodermal Dysplasia Group-Turkey, 2024)
Volume :13 Number : 2 (Page: 417-421)